MANDIBULR CONDYLE FRACTURE MANAGEMENT OUTCOME IN DEPARTMENT OF PLASTIC RECONSTRUCTIVE AND AESTHETIC SURGERY, DR. SOETOMO GENERAL ACADEMIC HOSPITAL (2015-2018) - Zarasade, Lobredia; Saputro, Iswinarno Doso; Putri, Nadia Tamara (Universitas Airlangga, 2020)
Highlights: The management of mandibular condyle fractures is determined based on patient age, fracture type, systemic health, other maxillofacial fractures, and dental conditions factors. Out of the total patients indicating successful management of mandibular condyle fractures at Dr. Soetomo Hospital. Abstract: Introduction: The high incidence of condyle mandible fractures is due to the role of the mandibular ramus which has stronger resistance compared to head condyle mandibular. The management of condyle fractures is still controversial because of the prognosis. Management of condyle fractures of the mandible should aim at maximally reducing morbidity, postoperative complications, and aesthetic and/ or functional impairment. Methods: The medical records of 56 patients with condyle mandible fractures who presented at the Dr. Soetomo General Academic Hospital Surabaya from January 2015 to December 2018 were reviewed retrospectively. We analyzed characteristics of the patients (age), type of fractures, management of fractures, and outcome from management. Results: This study shows that a total of 56 patients, 22 were patients with mandibular condyle fractures only and 34 patients with mandibular condyle fractures with other maxillofacial fractures. The studied showed that male patients (84%) is more than female patients (16%). The mean age of the patients involved in this study was 28.25 ± 1.78 years, with the youngest being 12 years old and the oldest being 67 years old. The results of the overall study with good occlusion results in 48 patients, it was found that 22 patients were treated with closed reduction and 26 patients with open reduction were performed. Conclusions: The results of condyle mandibula fracture management in Dr. Soetomo Hospital has been according to the indication with the treatment indication along with the result of good management.